The Influence of Managerial Skill, Principal Leadership Style and Compensation toward Teacher’s Performance - Ira Yuni Sari; Happy Fitria; Yenny Puspita (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2021)
This study determined the effect of managerial skills, principal leadership style, and compensation on teacher’s performance. This study used a correlation research method with an ex-post facto research design. The population in this study were all teachers in private high schools in Sekayu District, Musi Banyuasin Regency which consist of 48 people. The data collection technique used a questionnaire. Data were analyzed using multiple regression analysis techniques. The results showed that 1) there was an influence between managerial skills on teacher’s performance; 2) there was an influence between the leadership style of the principal on the performance of teachers; 3) there was an influence between compensation on teacher’s performance; and 4) there was a joint influence between managerial skills, leadership style of school principals, and compensation for teacher’s performance.